Educational Intervention on the Knowledge of Monkeypox Virus among Undergraduate Students in Rawalpindi; a Single Institution Quasi-Experimental Study - Hina Shan; Maryam Shan; Huzaifa Akram; Uzma Hassan; Raima Asif; Shazia Naqvi (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: The multi-country outbreak of Monkeypox (Mpox) in several regions has threatened the world, which is still confronted by the COVID-19 pandemic. To assess the effect of educational intervention on knowledge of epidemiology, prevention, and control of Monkeypox in undergraduate students. METHODOLOGY: The study is a single-institution educational intervention conducted from 1st July to 30th December 2022 among students enrolled in the Bachelor’s Program at the National University of Medical Sciences. The pre-post educational intervention without control groups using Quasi-experimental, non-randomized design was conducted among the study population through non-probability consecutive sampling. McNemar’s paired difference of proportions test was used to determine association. The p-value of ≤0.05 was considered statistically significant. RESULTS: The total sample of 79 students, 53 (67%) were females, with a mean age of 20.5±1.25 years. The knowledge regarding the epidemiology of the Mpox virus was relatively low in the pre-test, where only 10 (12.7%) students correctly identified this viral infection circulating in wildlife in Central and West Africa, also only 11 (13.6%) respondents had knowledge of the first human identification of Mpox in the 1970s in the Democratic Republic of the Congo. In Comparison of rightly chosen responses to correct and incorrect options regarding infection prevention and precautions for Mpox, only 24 (30.4%) respondents correctly identified the use of personal protective equipment (PPE) when caring for patients as significant, with 73(92.4%) agreeing to it in the post-test . Most respondents in the pre-test correctly identified the isolation of patients with Mpox p≤0.016